THE RELATIONSHIP BETWEEN MARKETING MIX AND PATIENT LOYALTY IN INTENSIVE CARE UNIT, ANUTAPURA PUBLIC HOSPITAL PALU - Napirah, Muhammad Ryman; Rau, Muh. Jusman; jah, Hadi (YCAB Publisher & IAKMI SULTRA, 2016)
Background: The problem generally faced by hospital is unable to provide something really needed by the customers. One of the main factors is the poor marketing mix of hospital that impacts to low quality and influences the patients loyality.Objective: The research aims to investigate the relationship between marketing mix and patient loyalty in intensive care unit at Anutapura Public Hospital Palu.Methods: This was a cross sectional study involving 97 persons who were randomly selected without considering the level of population. The data were analyzed thought univariat and bivariat on the significance level 95% (p<0,05). The marketing mix concept of 7P (product, price, place, promotion, people, process, dan physical evidence). Was used to guide this study.Results: The result of chi-square test indicated that there was a relationship of marketing mix product (p= 0,01), price (p= 0,00), promotion (p= 0,04), people (p= 0,00); and no relationship of marketing mix place (p= 0,21), process (p= 1,00), dan physical evidence (p= 1,00) with patient loyalty.Conclusion: It is expected tht the hospital of Anutapura Palu could increase the strategy of marketing mix for the sake of keeping the patients loyalty as the profit value of the hospital, especially for marketing place, process, and physical evidence.